Perceived use and value of reproductive, problem-solving, and athlete-initiated teaching by coaches and athletes - Kılıç, Koray; Ince, Mustafa Levent (Frontiers in Psychology, 2023)
In the sports coaching environment, it is recognized that developing athletes' autonomy and problem-solving skills are crucial to support holistic development and ensure optimal performance. However, there needs to be more information on how coaches use and value different teaching methods in training and how athletes perceive and value these methods. This study aimed to examine coaches' and athletes' perceptions of the use and value of reproductive, productive problem-solving, and productive athlete-initiated teaching methods. To this end, the Coaches' Use of Teaching Methods Scale which is validated for the use of coaches and athletes, was applied to 70 coaches and their 294 athletes of youth sports teams purposefully selected from four cities in Türkiye. Data were analyzed by nonparametric methods, including Friedman's and Mann-Whitney tests (p < .05). Although there were statistically significant differences between the responses of coaches and athletes regarding the use of different teaching methods in their training and the value they gave to these methods, both groups marked the frequent use of reproductive, occasional use of productive problem-solving and rare use of productive athlete-initiated teaching methods during training. The value given to productive athlete-initiated teaching methods in terms of enjoyment, learning, and motivation by the athletes was higher than the value given to them by the coaches. The study's findings strongly indicate the coaches' professional needs in their pedagogical knowledge, specifically on their value perceptions of productive problem-solving and productive athlete-initiated teaching methods and the capacity to apply them.